Health Insurance Exemptions for Older Ghanaians: Stakeholder Perspectives on Challenges Confronting an Ambitious Policy. Issue 4 (4th July 2022) - Alaazi, Dominic A.; Stafinski, Tania; Menon, Devidas
ABSTRACT: The health and wellbeing of older adults have taken center-stage in global policy agendas in recent times. In 2003, Ghana introduced an insurance exemption policy to eliminate financial barriers to healthcare for older adults and other vulnerable population groups. Embedded within the National Health Insurance Scheme (NHIS), this policy ostensibly guarantees free healthcare for older adults at publicly-funded facilities across the country. In this paper, we applied the implementation problem framework to identify gaps in the implementation of the exemptions policy and their impact on the healthcare experiences of older adults. Our data collection involved qualitative interviews with a purposive sample of community-residing older adults, health workers, community leaders, and policymakers. Our thematic data analysis identified resource, substantive, bureaucratic, political, and administrative constraints in the policy implementation process which, in turn, affected quality healthcare delivery. While most of these constraints are general challenges confronting the NHIS, they serve to undermine the intent of the scheme's exemptions policy. In particular, despite the exemptions, older adults continued to pay out-of-pocket for certain categories of treatments and medications, creating as yet financial barriers to healthcare. We present policy recommendations for addressing these implementation challenges, including suggestions to decentralize, depoliticize, and financially liberate the operations of the NHIS. Key points: Ghana's health insurance scheme has not eliminated financial barriers to healthcare for older adults. Older Ghanaians reported unmet healthcare needs, despite implementation of health insurance. Resource, substantive, bureaucratic, and political constraints impede the policy implementation process. Measures are needed to decentralize and depoliticize the NHIS implementation process.